PERTUKARAN BAHASA SEBAGAI SARANA PENDIDIKAN MULTIKULTURAL: PENGAJARAN BAHASA MELAYU RUMI OLEH MAHASISWA PGSD DI THAILAND SELATAN - Rahma Maesaroh; Ria Asyifah Riyani; Arsyi Rizqia Amalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Sampanvittaya School Thailand upholds the values of Malay culture. In multiculturaleducation, it emphasizes the importance of maintaining individual cultural identitywhile promoting equality and intercultural interaction. In school learning, Malaylanguage is one of the subjects in all classes. This Malay language learning is a formof preservation to maintain cultural identity carried out for students at this school.Based on the facts in the field, students at this school are less able to communicateusing Malay. The majority use Thai to communicate. This study aims to address thelack of ability of elementary school students at Sampanvittaya School, Narathiwat,Southern Thailand, in using Rumi Malay for daily communication. The researchmethodology was carried out in several phases, namely problem identification,problem formulation, solution formulation, material preparation, and teachingimplementation. This community service activity was carried out at SampanvittayaSchool for 25 days, starting from January 31 to February 24, 2025, and involved 255th grade elementary school students. The teaching process was carried out byElementary School Teacher Education (PGSD) students from MuhammadiyahUniversity of Sukabumi. The results show that this language exchange method iseffective not only for knowledge transfer, but also as a means for interaction andcultural understanding between Indonesia and Thailand.